The Contribution of Employment Vulnerability in Explaining Private Sector Inequality in Cameroon - NDAMSA, Dickson Thomas; NJANG, Gladys; BAYE, Francis Menjo (Asian Journal of Economic Modelling, 2017)
This paper identified the role of employment vulnerability and other regressed-income sources in accounting for private sector inequality and examined how much inequality in income and vulnerability is accounted for by within- and between-employment sector components in Cameroon. The paper employed two decomposition approaches: a regression-based framework and a Shapley Value-based rule. To attain these objectives, use was made of the 2007 Cameroon household consumption survey conducted by the government’s statistics office. Employment vulnerability accounted for about 4.1 percent to the national private sector income inequality of 0.38, meanwhile, labour market experience, years of schooling, infant dependency and urban residency accounted for about 6.4, 10.3, 7.0 and 14.2 percent, respectively. Results also showed that the within-group components overly accounted for the national private sector income Gini inequality. Whereas, over 87 percentage points of the within-sector inequality component of 92.5 percent was accounted for by the informal sector, inequality between the formal and informal sectors of employment was only 7.5 percent. These findings highlighted the heterogeneity of informal sector activities and the wisdom of designing policies that can entice transition from informality to formal sector activities.